2017
DOI: 10.1186/s12939-016-0509-3
|View full text |Cite
|
Sign up to set email alerts
|

Advancing system and policy changes for social and racial justice: comparing a Rural and Urban Community-Based Participatory Research Partnership in the U.S.

Abstract: BackgroundThe paper examines the role of community-based participatory research (CBPR) within the context of social justice literature and practice.MethodsTwo CBPR case studies addressing health inequities related to Type 2 Diabetes and Cardiovascular disease were selected from a national cross-site study assessing effective academic-community research partnerships. One CBPR partnership works with African Americans in rural Pemiscot County, Missouri and the other CBPR partnership works with African American an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…A new scoping review (Ortiz et al, 2020) identified 100 English-language reviews of distinct outcomes and populations since the groundbreaking Agency for Healthcare Research Quality 2004 review (Viswanathan et al, 2004). CBPR policy impacts on health have been well-documented (Cacari-Stone, Minkler, Freudenberg, & Themba, 2018;Minkler, Garcia, Rubin, & Wallerstein, 2012), and seen as equally important to partnership success as specific grant outcomes (Devia et al, 2017;Jagosh et al, 2012). Despite greater focus on outcomes, the science regarding effective CBPR lags practice, particularly how best to understand power-sharing practices that create pathways toward outcomes (Wallerstein, Muhammad, et al, 2019).…”
mentioning
confidence: 99%
“…A new scoping review (Ortiz et al, 2020) identified 100 English-language reviews of distinct outcomes and populations since the groundbreaking Agency for Healthcare Research Quality 2004 review (Viswanathan et al, 2004). CBPR policy impacts on health have been well-documented (Cacari-Stone, Minkler, Freudenberg, & Themba, 2018;Minkler, Garcia, Rubin, & Wallerstein, 2012), and seen as equally important to partnership success as specific grant outcomes (Devia et al, 2017;Jagosh et al, 2012). Despite greater focus on outcomes, the science regarding effective CBPR lags practice, particularly how best to understand power-sharing practices that create pathways toward outcomes (Wallerstein, Muhammad, et al, 2019).…”
mentioning
confidence: 99%
“…For example, Bronx Health REACH created policies to address SDOH at the local and state level. 22 They instituted school-based initiatives, including a policy to replace whole milk in all 1579 public schools and legislation requiring students to receive state-mandated physical education. 23 They launched #Not62 campaign for a healthy Bronx, which incorporates a community call to action for elected officials, faith-based leaders, health care executives, and community members to create the infrastructure needed to address social and economic factors to promote health equity 24 (“3.5” in Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, a community-based participatory research study implemented PSE change to overcome racial/social injustices in a rural community (Devia et al, 2017). PSE change interventions is also one strategy that CHCs in Indiana implement to reduce health disparities.…”
Section: Discussionmentioning
confidence: 99%